Typification of the name Galatella sorrentinoi (Asteraceae) - Di Gristina, Emilio; Scafidi, Filippo; Domina, Gianniantonio (Phytotaxa, 2020)
Tripolium sorrentinoi (Todaro 1858: 42) Raimondo & Greuter (2005: 59) (Asteraceae) is a species endemic to Sicily. In this island, it grows on badlands in the Palermo, Enna, Caltanissetta, and Agrigento Provinces, between the coast and the hinterland mountains. Its phytogeographical interest is remarkable because it occurs in selective habitats, where it is often the sole phanerogamic inhabitant. Due to its small population size and to a continuing decline of mature individuals, T. sorrentinoi was assessed as “Vulnerable” (VU) according to the IUCN criteria (Domina & Troia 2016).